More Than Food: The Social Benefits of Localized Urban Food Systems - Diekmann, Lucy O.; Gray, Leslie C.; Thai, Chan Le (Frontiers in Sustainable Food Systems, 2020)
Localized urban food systems are gaining attention from policy makers, planners, and advocates for benefits that go well beyond food production and consumption. Recognizing that agriculture, and food systems more broadly, provide multiple, integrated services, this study measures the social, educational, civic, and nutritional impacts of four common types of local food system activity in an urban setting. Specifically, we examine the outcomes of two common types of urban agricultural production (home gardens and community gardens) and two common types of direct markets (farmers’ markets and Community Supported Agriculture programs or CSAs) through a survey of 424 gardeners and 450 direct market shoppers in California’s San Francisco Bay Area. Our comparative analysis focuses on four commonly discussed functions of agricultural production and direct marketing in urban areas: access to high-quality, fresh produce; food and agriculture education; social connections; and civic engagement. While impacts on nutrition were consistently high, some of the largest differences between types of local food system activities were in social interaction and civic engagement. For example, gardeners had a mean score of 3.77 on the social interaction scale compared to direct market participants, who had a mean score of 3.03. These findings confirm that different types of local production and direct marketing have distinct impacts on participants. Generally, gardens, which involve more sustained engagement with other people and the natural world, were sites of greater learning, connection, and civic participation than either type of direct marketing.